Knowledge of pregnancy danger signs and associated factors among pastoral women in Afar Regional State, Ethiopia - Misgan Legesse Liben; Abel Gebre Wuneh; Nejimu Biza Zepro (Cogent Medicine, 2019)
Introduction: Knowledge of pregnancy danger sign is the vital step in receiving appropriate and timely referral to maternal and newborn care units. Therefore, the current analysis assesses knowledge of pregnancy danger signs and associated factors among women who gave birth in the two years preceding the survey among pastoralist communities in Afar Regional State, Northeastern Ethiopia. Methods: A cross-sectional study was employed in Afar National Regional State in February 2016. A multistage cluster sampling was employed to select study women. Data were cleaned, coded and entered into EpiData version 3.02, and were exported to SPSS version 20 statistical package for analysis. Results: Eighty-nine [7.9; 95% CI (6–9%)] of the study women knew at least two key pregnancy danger signs. Women who attended antenatal care visit [AOR: 4.88; 95% CI (2.83, 8.41)], who had more than three family members [AOR: 2.25; 95% CI (1.26, 4.01)] and who attended formal education [AOR: 2.0; 95% CI (1.15, 3.47)] were positively associated with knowledge of key pregnancy danger signs. On the other hand, women who reported pastoralist as their occupation were associated with lower odds of knowledge on key pregnancy danger signs [AOR: 0.60; 95% CI (0.437, 0.831)]. Conclusion: This study showed that nearly 1 women in every 13 had knowledge on key danger signs of pregnancy. Therefore, strengthening pastoralist-based maternal health information system could be important to improve maternal knowledge of pregnancy danger signs in Afar Regional State.